Laminate and method for producing laminate

By using a grafted modified body of a carbodiimide group and a polymerizable double bond in a laminate of fluororesin, liquid crystal polymer, ABS-based resin and polyketone-based resin, the problem of poor bonding strength is solved, and the problem of achieving the achievement of the Made of laminated bodies with high bonding strength and stability.

CN119156285APending Publication Date: 2024-12-17MITSUI CHEMICALS INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380038535.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-05-25
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the bonding strength between fluororesin, liquid crystal polymer (LCP), acrylonitrile-butadiene-styrene copolymer resin (ABS resin) and polyketone resin is poor, which limits the majority of them. Application in laminated laminates.

Method used

The polyolefin is grafted and modified by carbodiimide monomers of carbonidiimide groups and polymerizable double bonds to form a bonding composition, and is coextruded, laminated, blow molded or co-injected The molding method is used to manufacture the laminated body to ensure high bonding strength of the bonding layer.

Benefits of technology

It has achieved excellent interlayer bonding between fluororesin, LCP, ABS resin and polyketone resin, enhanced the overall bonding strength and stability of the laminated body, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118942300000031
    Figure BDA0005118942300000031
  • Figure BDA0005118942300000051
    Figure BDA0005118942300000051
  • Figure BDA0005118942300000101
    Figure BDA0005118942300000101
Patent Text Reader

Abstract

One embodiment of the present invention relates to: a laminate provided with a layer (A) containing at least one resin selected from the group consisting of a fluororesin, an LCP, an ABS-based resin and a polyketone-based resin, and a bonding layer (B) containing a bonding composition, at least a part of the bonding layer (B) being in contact with the layer (A); the bonding composition contains a graft-modified body obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond, the bonding composition contains 0.1-50 mmol of carbodiimide group per 100 g of the bonding composition, and the bonding composition has a density of 0.870-0.940 g / cm3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a laminate and a method for producing the laminate. Background Art

[0002] Fluororesins such as polytetrafluoroethylene, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and ethylene / tetrafluoroethylene copolymers have been used in various fields such as the semiconductor industry and the automotive industry due to their excellent heat resistance, chemical resistance, oil resistance, weather resistance, gas barrier properties, fuel barrier properties, mold release properties, non-adhesive properties, and stain resistance. As the use of fluororesins expands, multilayer laminates of fluororesins and thermoplastic resins other than fluororesins with excellent mechanical strength have been studied in scenarios where it is necessary to improve the mechanical strength of fluororesins and reduce costs.

[0003] Liquid crystal polymer (hereinafter referred to as "LCP") has excellent chemical resistance, gas barrier properties, etc., and is expected to be used in container packaging materials, automobile fuel tanks, etc. However, LCP generally has the property of being highly oriented along the flow direction during the melting process. Therefore, although its strength in the molding direction is high, it has the disadvantage of being weak in the direction substantially perpendicular to the molding direction. In addition, since it is also expensive, its use in lamination with other resin layers has been studied.

[0004] Acrylonitrile-butadiene-styrene copolymer resin (hereinafter also referred to as "ABS resin") has excellent properties in mechanical strength, rigidity, heat resistance, chemical corrosion resistance, oil resistance, transparency, low-temperature impact resistance, etc., and can be widely used as packaging materials / wrapping materials such as films, sheets, bottles, or decorative materials such as wallpaper by utilizing these properties.

[0005] Polyketone resins are expected to be used as food preservation or food packaging materials due to their excellent gas barrier properties. Since polyketone resins have poor thermal bonding performance and impact strength when used directly, they are preferably used in the form of a laminate with other resins such as polyolefins.

[0006] However, it is known that the functional groups on the resin surfaces of fluororesins and LCPs have poor reactivity with the functional groups on the surfaces of other resins (e.g., maleic anhydride-modified resins known in the past), and thus the bonding properties with other resins are poor. In particular, LCP is known to have a low surface free energy among resins, and thus the bonding properties with other resins are particularly poor.

[0007] For these reasons, the application of lamination of fluororesins and LCP with other materials is limited.

[0008] Furthermore, it is known that the functional groups present in ABS-based resins, polyketone-based resins, and the like have particularly poor reactivity with other resins, and therefore have particularly poor bonding properties.

[0009] Therefore, the lamination application of ABS resins, polyketone resins and other materials is restricted, and it is usually difficult to select ABS resins and polyketone resins as resins for lamination with other materials.

[0010] In order to solve such problems, Patent Document 1 discloses a multilayer laminate having a laminate structure in which a layer formed of a fluororesin containing an acid anhydride residue and a layer formed of an amine-modified thermoplastic resin are directly laminated as a multilayer laminate with high interlayer adhesion.

[0011] In addition, as a bonding resin having good bonding properties with LCP, Patent Document 2 discloses a modified polyolefin obtained by graft-polymerizing a specific polyolefin with an ethylenically unsaturated monomer containing an epoxy group, and a bonding resin composition containing the polyolefin.

[0012] In addition, Patent Document 3 discloses a laminated body formed by melt coextrusion of a thermoplastic resin such as an ABS resin and a polyolefin resin. Since the protective film formed by the polyolefin resin satisfies specified parameters, it has both suppression of brightness unevenness and specific bonding strength.

[0013] Patent Document 4 discloses a laminate in which a polymethylpentene resin layer and a polyketone layer are well bonded by providing an adhesive layer containing a predetermined component between the polyketone layer and a predetermined polymethylpentene resin layer.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: International Publication No. 2005 / 068191

[0017] Patent Document 2: International Publication No. 2003 / 078488

[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 2013-184466

[0019] Patent Document 4: International Publication No. 2020 / 145239 Summary of the invention

[0020] However, with the improvement of physical property requirements in recent years, it is necessary to realize a laminate having a higher bonding strength than the laminate described in the above-mentioned patent documents 1 to 4 in a laminate containing a layer of at least one resin selected from fluororesin, LCP, ABS resin and polyketone resin and a bonding layer.

[0021] One embodiment of the present invention provides a laminate having excellent bonding strength between a layer containing at least one resin selected from fluororesins, LCP, ABS-based resins and polyketone-based resins and a bonding layer, and a method for producing the same.

[0022] Technical solutions to solve problems

[0023] The configuration examples of the present invention are as follows.

[0024] [1] A laminate comprising: a layer (A) containing at least one resin selected from the group consisting of a fluororesin, a liquid crystal polymer, an acrylonitrile-butadiene-styrene copolymer resin and a polyketone resin; and a bonding layer (B) containing a bonding composition,

[0025] At least a portion of the bonding layer (B) is in contact with the layer (A),

[0026] The above-mentioned bonding composition satisfies the following requirements (i) to (iii):

[0027] (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond;

[0028] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition;

[0029] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0030] [2] The laminate according to [1], wherein the carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2),

[0031]

[0032] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

[0033] [3] The laminate according to [1] or [2], wherein the layer (A) is made of a fluororesin.

[0034] [4] The laminate according to [3], wherein the fluororesin is an acid-modified fluororesin.

[0035] [5] The laminate according to [1] or [2], wherein the layer (A) is made of a liquid crystal polymer.

[0036] [6] The laminate according to [1] or [2], wherein the layer (A) is made of an acrylonitrile-butadiene-styrene copolymer resin.

[0037] [7] The laminate according to [1] or [2], wherein the layer (A) is made of a polyketone resin.

[0038] [8] The laminate according to any one of [1] to [7], wherein the laminate is obtained by coextrusion molding, lamination molding, blow molding or coinjection molding.

[0039] [9] A method for producing a laminate, wherein the laminate comprises: a layer (A) containing at least one resin selected from the group consisting of a fluororesin, a liquid crystal polymer, an acrylonitrile-butadiene-styrene copolymer resin and a polyketone resin; and a bonding layer (B) containing a bonding composition, wherein at least a portion of the bonding layer (B) is in contact with the layer (A);

[0040] The manufacturing method comprises the steps of: co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins with the bonding composition;

[0041] The above-mentioned bonding composition satisfies the following requirements (i) to (iii):

[0042] (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond;

[0043] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition;

[0044] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0045]

[10] The method for producing a laminate according to [9], wherein the carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2),

[0046]

[0047] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

[0048]

[11] The method for producing a laminate according to [9] or

[10] , wherein the layer (A) is made of a fluororesin.

[0049]

[12] The method for producing a laminate according to

[11] , wherein the fluororesin is an acid-modified modified fluororesin.

[0050]

[13] The method for producing a laminate according to [9] or

[10] , wherein the layer (A) is made of a liquid crystal polymer.

[0051]

[14] The method for producing a laminate according to [9] or

[10] , wherein the layer (A) is made of an acrylonitrile-butadiene-styrene copolymer resin.

[0052]

[15] The method for producing a laminate according to [9] or

[10] , wherein the layer (A) is made of a polyketone resin.

[0053] Effects of the Invention

[0054] According to one embodiment of the present invention, there can be provided a laminate having excellent bonding strength between a layer containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins and a bonding layer, and a method for producing the same. DETAILED DESCRIPTION

[0055] "Laminated Body"

[0056] A laminated body according to one embodiment of the present invention comprises: a layer (A) containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins; and a bonding layer (B) containing a bonding composition, wherein at least a portion of the layer (B) is in contact with the above-mentioned layer (A).

[0057] Since the laminate includes the layer (B), it is possible to obtain a laminate that is excellent in interlayer adhesion and in which interlayer adhesion is unlikely to decrease.

[0058] The laminate is not particularly limited as long as it contains the layer (A) and the layer (B). It may contain two or more layers of the layer (A) or two or more layers of the layer (B). When it contains two or more layers of the layer (A), these layers may be the same layer or different layers. In addition, similarly, when it contains two or more layers of the layer (B), these layers may be the same layer or different layers.

[0059] The above-mentioned laminate is preferably a laminate comprising layer (A) and layer (B), particularly preferably a laminate consisting of layer (A) and layer (B), or a laminate comprising layer (A), layer (B) and layer (A) in sequence, particularly preferably a laminate in which layer (A), layer (B) and layer (A) are stacked in sequence.

[0060] In addition, as a laminate including the above-mentioned layer (A) and layer (B), for example, a laminate including layer (A), layer (B), and layer (C) in this order may be sufficient.

[0061] The layer (C) is not particularly limited as long as it is a layer other than layer (A) and layer (B). Examples thereof include layers containing thermoplastic resins such as metal, glass, wood, paper, cloth, polyester, polyphenylene sulfide, polyamide, polyacetal, polycarbonate, poly(meth)acrylate, olefin polymers, polystyrene, rubber, biomass plastics, and other engineering plastics, layers of thermosetting resins, or layers composed of these layer materials.

[0062] The laminate is not limited to the shape of a laminate film (sheet), and may be any of various known shapes such as a hollow container, a cup, and a tray.

[0063] The laminate is preferably a laminate obtained by co-extrusion molding, lamination molding, blow molding or coinjection molding from the viewpoint of easily obtaining a laminate having excellent bonding strength.

[0064] <Layer(A)>

[0065] The layer (A) is not particularly limited as long as it contains at least one resin selected from fluororesins, LCP, ABS resins and polyketone resins, and is preferably a layer consisting (only) of fluororesins, LCP, ABS resins and polyketone resins.

[0066] The above-mentioned fluororesins, LCPs, ABS-based resins and polyketone-based resins may be resins using only biomass-derived raw materials, only fossil fuel-derived raw materials, or both biomass-derived raw materials and fossil fuel-derived raw materials as raw materials.

[0067] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the fluororesins, LCPs, ABS-based resins, and polyketone-based resins are preferably resins made from biomass-derived raw materials.

[0068] The fluororesin is not particularly limited, but examples thereof include polymers of fluorine-containing monomers, copolymers of fluorine-containing monomers, and copolymers of fluorine-containing monomers and monomers other than fluorine-containing monomers.

[0069] As the above-mentioned fluororesin, one kind may be used, or two or more kinds may be used.

[0070] Examples of the fluorinated monomer include tetrafluoroethylene (hereinafter referred to as "TFE"), trifluoroethylene, vinylidene fluoride (hereinafter referred to as "VDF"), vinyl fluoride, chlorotrifluoroethylene (hereinafter referred to as "CTFE"), hexafluoropropylene (hereinafter referred to as "HFP"), CF2=CFRf (wherein Rf is a polyfluoroalkyl group having 2 to 10 carbon atoms), CH2=CX(CF2) n Y (wherein X and Y are each independently a hydrogen atom or a fluorine atom, and n is an integer from 2 to 8), fluorinated olefins such as compounds represented by CF2=CFO(CF2)2F, CF2=CFO(CF2)3F (hereinafter also referred to as "PPVE"), perfluoro(alkyl vinyl ethers) such as CF2=CFOCH2CF3, and (polyfluoroalkyl)trifluorovinyl ethers containing hydrogen atoms such as CF2=CFOCH2CF3. Preferably, the fluorinated olefins are selected from TFE, VDF, PPVE and CH2=CX(CF2). n One or more of Y. More preferably, it is TFE.

[0071] The fluorine-containing monomer may be used alone or in combination of two or more.

[0072] Monomers other than the above-mentioned fluorine-containing monomers include hydrocarbon olefins such as ethylene (hereinafter also referred to as "E"), propylene, and butene, vinyl ethers such as ethyl vinyl ether, butyl vinyl ether, methyl vinyl oxybutyl carbonate, and glycidyl vinyl ether, and vinyl esters such as vinyl acetate, vinyl chloroacetate, vinyl butyrate, vinyl tert-valerate, vinyl benzoate, and vinyl crotonate. Ethylene is preferred.

[0073] The monomers other than the fluorine-containing monomer may be used alone or in combination of two or more.

[0074] Specific examples of the fluororesin include TFE / E-based copolymers, TFE / HFP-based copolymers, TFE / PPVE-based copolymers, TFE / VDF / HFP-based copolymers, TFE / VDF-based copolymers, and CTFE / E-based copolymers.

[0075] The fluororesin may be a modified fluororesin, but a modified fluororesin is preferred from the viewpoint of better exerting the effects of the present invention. The modified fluororesin is not limited, but an acid-modified fluororesin may be mentioned.

[0076] Examples of the acid-modified fluororesin include resins obtained by modifying the above-mentioned fluororesins with at least one selected from unsaturated carboxylic acids and derivatives thereof (particularly acid anhydrides).

[0077] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylic acid.

[0078] Examples of the derivatives of the unsaturated carboxylic acid include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylic anhydride.

[0079] Among the unsaturated carboxylic acids and derivatives thereof, maleic anhydride is preferred.

[0080] The content of the acid group and the acid anhydride group in the acid-modified fluororesin is preferably 0.01 to 3 mol %, more preferably 0.05 to 2 mol %, and even more preferably 0.1 to 1 mol %, based on 100 mol % of all structural units constituting the fluororesin.

[0081] The LCP is not limited, but examples thereof include aromatic polyesters and / or aromatic polyester amides generally referred to as thermotropic liquid crystal polymers.

[0082] As the LCP, one kind may be used, or two or more kinds may be used.

[0083] As a specific example of the above-mentioned LCP, there can be mentioned

[0084] (1) using aromatic dicarboxylic acids, aromatic diols and aromatic hydroxycarboxylic acids as reactants;

[0085] (2) using different kinds of aromatic hydroxycarboxylic acids as reactants;

[0086] (3) using aromatic dicarboxylic acids and core-substituted aromatic diols as reactants;

[0087] (4) A reaction product obtained by reacting an aromatic hydroxycarboxylic acid or the like with a polyester such as polyethylene terephthalate.

[0088] In addition, instead of these aromatic dicarboxylic acids, aromatic diols, and aromatic hydroxycarboxylic acids, their ester-forming derivatives may be used.

[0089] The LCP is preferably a liquid crystal polymer comprising structural units derived from one or more of the following monomers, usually at least two of the following monomers:

[0090] Terephthalic acid, isophthalic acid, 1,4-hydroquinone, resorcinol, 4-aminobenzoic acid, 4-hydroxybenzoic acid, 4-aminophenol, 1,4-phenylenediamine, 4,4'-bisphenol, 4,4'-biphenyldicarboxylic acid, 6-hydroxy-2-naphthoic acid, 2,6-naphthalene dicarboxylic acid, 2,6-dihydroxynaphthalene.

[0091] The ABS resin is a general term for resins obtained by copolymerizing acrylonitrile, butadiene, and styrene as raw material monomers.

[0092] The ABS resin also includes resins using, as raw material monomers for synthesis of the resin, methacrylonitrile, ethacrylonitrile, fumaronitrile or the like in addition to acrylonitrile or in place of acrylonitrile (acrylonitrile-substitute component).

[0093] In addition, ABS-based resins also include resins in which monomers (butadiene replacement components) such as acrylic rubber based on butyl (meth)acrylate, chlorinated polyethylene, and ethylene-propylene-diene (EPDM) based on ethylene-based rubber are used in addition to butadiene or in place of butadiene.

[0094] The ABS resin also includes resins using, as raw material monomers for synthesizing the resin, α-methylstyrene, vinyltoluene, dimethylstyrene, chlorostyrene, vinylnaphthalene, etc. (styrene substitute components) in addition to styrene or in place of styrene.

[0095] Therefore, in this specification, ABS-based resin is a concept including AES-based resin, ASA-based resin, ACS-based resin, and the like.

[0096] As the ABS-based resin, one kind may be used, or two or more kinds may be used.

[0097] The ratio of the structural units derived from each component in the ABS resin is not particularly limited, but the content of the structural units derived from acrylonitrile or an acrylonitrile substitute component is preferably 10 to 89% by mass, the content of the structural units derived from butadiene or a butadiene substitute component is preferably 1 to 80% by mass, and the content of the structural units derived from styrene or a styrene substitute component is preferably 10 to 89% by mass.

[0098] As the ABS resin, resins synthesized by known methods such as bulk polymerization, solution polymerization, bulk suspension polymerization, suspension polymerization, and emulsion polymerization may be used, and commercially available resins may also be used.

[0099] Examples of the commercially available products include KRALASTIC (manufactured by Nippon A&L Inc.), SANTAC (manufactured by Nippon A&L Inc.), CYCOLAC (manufactured by Techno-UMG Co., Ltd.), and TECHNO ABS (manufactured by Techno Polymer).

[0100] The polyketone resin is a resin other than fluororesin, LCP and ABS resin.

[0101] Examples of polyketone resins include chain polymers formed by alternating bonds between a carbonyl group (CO) and a divalent organic group derived from an ethylenically unsaturated compound or two or more divalent organic groups of the organic group. Typical examples include resins represented by the following formula (3).

[0102] The polyketone resin can be obtained, for example, by polymerizing carbon monoxide and an ethylenically unsaturated compound by a known method.

[0103] As the polyketone resin, one kind may be used, or two or more kinds may be used.

[0104]

[0105] In formula (3), A is a divalent organic group derived from an ethylenically unsaturated compound, and m is an integer of 1 to 6. n is an integer of 2 or more, and preferably an integer of 2 to 6,000.

[0106] Examples of the olefinic unsaturated compound include α-olefins having 2 to 12 carbon atoms, such as ethylene, propylene, 1-butene, isobutylene, and 1-pentene, preferably linear α-olefins having 2 to 6 carbon atoms, more preferably only ethylene, or ethylene and propylene.

[0107] Butadiene, isoprene, 2-chloro-1,3-butadiene and other dienes or their halides;

[0108] Vinylidene chloride and other vinylidene diolefins or their halides;

[0109] Vinyl esters such as vinyl acetate, vinyl chloroacetate, dimethyl vinyl acetate, trimethyl vinyl acetate, or their halides;

[0110] Vinyl halides such as tetrafluoroethylene and vinyl chloride;

[0111] Vinyl acetals such as ketomethyl (vinyl) acetal;

[0112] Vinyl ketones such as methyl vinyl ketone and ethyl vinyl ketone;

[0113] Styrene, chlorostyrene, α-methylstyrene and other styrenes or their derivatives;

[0114] Acrylic acid and methacrylic acid, their esters, amidates, nitriles and acyl halides;

[0115] Vinyl esters of unsaturated carboxylic acids such as vinyl hexenoate and vinyl crotonate.

[0116] As the ethylenically unsaturated compound, linear α-olefins having 2 to 6 carbon atoms are preferred, and those containing only ethylene or ethylene and propylene are particularly preferred.

[0117] Therefore, as the polyketone-based resin, ethylene / carbon monoxide copolymers and ethylene / propylene / carbon monoxide copolymers are preferred.

[0118] The above-mentioned olefinic unsaturated compounds may be used alone or in combination of two or more. In the latter case, it is preferred to use ethylene in combination with a linear α-olefin having 3 to 6 carbon atoms, particularly ethylene and propylene. In this case, the molar ratio of ethylene to a linear α-olefin having 3 to 6 carbon atoms is preferably greater than 1, more preferably 2 to 30.

[0119] As the polyketone-based resin, commercially available products may be used.

[0120] Examples of the commercially available products include AKROTEK: PK-HM (manufactured by AKRO-PLASTIC) and Carilon (manufactured by Shell).

[0121] The layer (A) may contain additives such as phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, metal compounds, and metal salts of higher fatty acids, which are generally used for adding to resins, as necessary, within the range not impairing the purpose of the present invention.

[0122] The additive may be an additive using only a biomass-derived raw material as its raw material, an additive using only a fossil fuel-derived raw material, or an additive using both a biomass-derived raw material and a fossil fuel-derived raw material.

[0123] The thickness of the layer (A) is not particularly limited and may be appropriately selected depending on the intended use of the laminate, but is preferably 2 to 1000 μm.

[0124] <Joint layer (B)>

[0125] The layer (B) is a layer containing a bonding composition (hereinafter also referred to as "the composition of the present invention") and can be obtained using the composition of the present invention.

[0126] The content of the composition of the present invention in the layer (B) is preferably 80 to 100% by mass, more preferably 90 to 100% by mass.

[0127] The thickness of the layer (B) is not particularly limited and may be appropriately selected depending on the intended use of the laminate, but is preferably 2 to 1000 μm.

[0128] [Joining composition]

[0129] The composition of the present invention satisfies the following requirements (i) to (iii):

[0130] (i) a graft modified product obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond (hereinafter also referred to as "the modified product of the present invention");

[0131] (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the composition of the present invention;

[0132] (iii) Density: 0.870 to 0.940 g / cm 3 .

[0133] The content of the carbodiimide group in the composition of the present invention is 0.1 to 50 mmol, preferably 0.2 to 20 mmol, more preferably 0.5 to 5 mmol per 100 g of the composition of the present invention.

[0134] When the carbodiimide group content is within the above range, it is possible to easily obtain the composition of the present invention which can be firmly bonded to the body to be bonded, especially a layer containing at least one resin selected from fluororesin, LCP, ABS resin and polyketone resin, even at a low temperature at which the fluororesin, LCP, ABS resin and polyketone resin do not thermally decompose.

[0135] The carbodiimide group content is specifically measured by the method described in the following examples.

[0136] The density of the composition of the present invention measured according to JIS K 7210 is 0.870 to 0.940 g / cm 3 , preferably 0.880 to 0.925 g / cm 3 , more preferably 0.890 to 0.920 g / cm 3 .

[0137] When the density is within the above range, it is easy to obtain the composition of the present invention which can be firmly bonded even to the objects to be bonded, especially to a layer containing at least one resin selected from fluororesins, LCPs, ABS resins and polyketone resins, at a low temperature at which the fluororesins, LCPs, ABS resins and polyketone resins do not thermally decompose.

[0138] The melt flow rate (MFR) of the composition of the present invention measured at 190°C and under a load of 2.16 kg in accordance with JIS K 7210 is preferably 0.1 to 10 g / 10 min, more preferably 0.2 to 5 g / 10 min.

[0139] When the MFR is within the above range, a desired laminate can be easily formed by a molding method such as co-extrusion molding, lamination molding, blow molding, and coinjection molding, which is preferred.

[0140] The composition of the present invention is not particularly limited as long as it contains the modified product of the present invention, and may consist only of the modified product of the present invention.

[0141] Since the composition of the present invention contains the modified product of the present invention, a layer having high bonding strength with an object to be bonded, particularly a layer containing at least one resin selected from fluororesins, LCP, ABS resins and polyketone resins, can be formed even in a short time.

[0142] Since the modified body of the present invention has higher reactivity with polar groups present in fluororesins, LCPs, ABS resins, polyketone resins, etc. than graft modified bodies modified with glycidyl (meth)acrylate or acid / acid anhydride, the composition containing the modified body of the present invention has significantly excellent adhesion to a layer containing at least one resin selected from fluororesins, LCPs, ABS resins, and polyketone resins.

[0143] Since the modified product of the present invention is not a block copolymer or a random copolymer of an olefin monomer such as ethylene or propylene and the above-mentioned carbodiimide monomer but a graft modified product, the composition of the present invention can exert the above-mentioned effects by using the modified product of the present invention.

[0144] The modified product of the present invention may be used in the composition of the present invention in the form of one species or in the form of two or more species.

[0145] The content of the modified product of the present invention in the composition of the present invention is not particularly limited, but from the perspectives of molding processability, controllability of bonding performance, economic benefits, etc., it is usually 0.5 mass% or more, preferably 1 mass% or more, and usually 60 mass% or less, preferably 50 mass% or less.

[0146] The composition of the present invention preferably contains the modified product of the present invention and one or more olefin-based polymers other than the modified product of the present invention.

[0147] The olefin polymers that can be used in the composition of the present invention are not particularly limited, and any known olefin polymers can be used as long as they are polymers made of olefins. Specifically, homopolymers or copolymers of α-olefins such as ethylene, propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene (e.g., high-pressure low-density polyethylene, linear low-density polyethylene (LLDPE), medium-density polyethylene, high-density polyethylene, polypropylene, poly(1-butene), poly(4-methyl-1-pentene), low-crystalline or amorphous ethylene / propylene random copolymers, ethylene / 1-butene random copolymers, propylene / 1-butene random copolymers), ethylene / vinyl acetate copolymers (EVA) or saponified products thereof, ethylene / (meth)acrylic acid copolymers or metal salts thereof (ionomers), ethylene / cycloolefin copolymers, and polymers obtained by grafting and modifying these polymers / copolymers with polar compounds such as maleic acid and silane compounds.

[0148] Among them, in the case of the modified product of the present invention contained in the composition of the present invention, from the perspective of being able to easily obtain a composition of the present invention with excellent compatibility and better able to exert the desired effect, the above-mentioned olefin-based polymer is preferably the same polymer as the base polymer used to synthesize the modified product of the present invention.

[0149] The olefin-based polymer may be a polymer using only biomass-derived raw materials as its raw materials (eg olefins), a polymer using only fossil fuel-derived raw materials, or a polymer using both biomass-derived raw materials and fossil fuel-derived raw materials.

[0150] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the olefin-based polymer is preferably a polymer made from a biomass-derived raw material.

[0151] In this specification, biomass-derived raw materials refer to raw materials formed from any (renewable) natural raw materials of plant or animal origin, including fungi, yeast, algae and bacteria, and their residues, such as carbon-containing 14 C isotope 1×10 ﹣12 The ratio of the raw material to the carbon content of the biomass is about 100 pMC, and the biomass carbon concentration (unit: pMC) measured according to ASTM D6866 is about 100 pMC. The raw material derived from biomass can be obtained by, for example, a conventionally known method.

[0152] For a certain polymer, when the production conditions of the polymer such as the polymerization catalyst, polymerization process, polymerization temperature, etc. are determined, even if the polymer contains biomass-derived raw materials, 14 C isotope 1×10 ﹣12 ~1×10 ﹣14The molecular structure except for the ratio of the above proportions is equivalent to that of the polymer formed from the raw material derived from fossil fuels. Therefore, it can be considered that the performance of the polymer containing the raw material derived from biomass is the same as that of the polymer containing the raw material derived from fossil fuels.

[0153] When the composition of the present invention contains the above-mentioned olefin-based polymer, the content of the olefin-based polymer in the composition of the present invention is not particularly limited, but is usually 40% by mass or more, preferably 50% by mass or more, and usually 99.5% by mass or less, preferably 99% by mass or less, from the perspectives of molding processability, controllability of bonding performance, economic benefits, etc.

[0154] The composition of the present invention may contain various additives other than the modified product of the present invention and the above-mentioned olefin polymer as necessary within the range not impairing the purpose of the present invention.

[0155] Examples of the additive include softeners, stabilizers, fillers, antioxidants, crystal nucleating agents, waxes, thickeners, mechanical stability enhancers, leveling agents, wetting agents, film-forming aids, crosslinking agents, preservatives, rust inhibitors, pigments, dispersants, antifreeze agents, defoamers, viscosity enhancers, other thermoplastic polymers, water, and organic solvents. These additives may be used alone or in combination of two or more.

[0156] The additive may be an additive using only biomass-derived raw materials, an additive using only fossil fuel-derived raw materials, or an additive using both biomass-derived raw materials and fossil fuel-derived raw materials.

[0157] The composition of the present invention can be used in various known adhesive forms, such as water-dispersible adhesives, organic solvent-based adhesives, and hot-melt adhesives.

[0158] <Modified product of the present invention>

[0159] The modified product of the present invention is a graft modified product obtained by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond. In other words, it is a graft modified product obtained by grafting at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond. The modified product of the present invention can also be said to be a graft modified product comprising at least one base polymer portion selected from polyolefins and a graft portion derived from a carbodiimide monomer having a carbodiimide group and a polymerizable double bond.

[0160] The fact that the layer (B) contains the modified product of the present invention can be determined by infrared spectroscopy.

[0161] From the viewpoints of easy synthesis of the modified product of the present invention, easy acquisition of the graft modified product with better bonding properties, and the fact that the obtained graft modified product does not become too hard, the graft rate in the modified product of the present invention is preferably 0.3 to 7% by mass, more preferably 0.5 to 5% by mass.

[0162] The grafting rate is the quality of the structure derived from the carbodiimide monomer in the grafted modified body, which can be measured by 1 H-NMR measurement was specifically obtained by the method described in the following Examples.

[0163] [Carbodiimide monomer]

[0164] The carbodiimide monomer used for graft modification of the above-mentioned base polymer is not particularly limited as long as it is a compound having a carbodiimide group and a polymerizable double bond. However, from the perspective of better exerting the effects of the present invention, a compound represented by the following formula (1) or (2) is preferred.

[0165] The carbodiimide monomers used for graft modification of the above-mentioned base polymer may be two or more, but are usually one.

[0166] The carbodiimide monomer may be a monomer derived from biomass, a monomer derived from fossil fuels, or a monomer derived from both biomass and fossil fuels.

[0167] From the viewpoint of reducing environmental load (mainly reducing greenhouse gas), the carbodiimide monomer is preferably a monomer derived from biomass or a monomer derived from biomass and fossil fuels.

[0168]

[0169] In the formula (1), R1 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom from the viewpoint of easily obtaining the modified product of the present invention having a high grafting rate.

[0170] In formula (1), R2 is an alkyl group or an aryl group which may have a substituent. The alkyl group which may have a substituent may be a chain (either straight chain or branched) or may contain an alicyclic ring.

[0171] The number of carbon atoms in the alkyl group which may have a substituent is preferably 1 or more, more preferably 3 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less. In addition, the number of carbon atoms in the aryl group which may have a substituent is preferably 5 or more, more preferably 6 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less.

[0172] Examples of the substituent which the alkyl group and the aryl group may have include a halogen atom, a hydrocarbon group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a carboxylate group having 1 to 8 carbon atoms, a sulfonate group having 1 to 8 carbon atoms, a carbonyl group having 1 to 8 carbon atoms, an amide group having 1 to 8 carbon atoms, an amino group having 1 to 8 carbon atoms, a thioether group having 1 to 8 carbon atoms, a phosphate group having 1 to 8 carbon atoms, an alkylsilyl group having 1 to 8 carbon atoms, and an alkoxysilyl group having 1 to 8 carbon atoms.

[0173] Among them, from the viewpoints of solubility and availability of the carbodiimide monomer and easy purification of the obtained graft modified product, R2 is preferably an aliphatic hydrocarbon group having 4 to 20 carbon atoms including an alicyclic ring, and more preferably an alicyclic hydrocarbon group having 5 to 7 carbon atoms.

[0174] Examples of the alicyclic ring include cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and the above rings having a hydrocarbon group. In addition, the alicyclic ring may be a polycyclic ring such as an adamantyl ring and a methyladamantyl ring.

[0175]

[0176] In formula (2), R3 is a hydrogen atom or a methyl group, and is preferably a methyl group from the viewpoint of being able to easily obtain the composition of the present invention having excellent bonding strength with a layer containing at least one resin selected from fluororesins, LCP, ABS resins and polyketone resins.

[0177] In formula (2), R4 is an alkyl group or an aryl group which may have a substituent. The alkyl group which may have a substituent may be a chain (may be straight chain or branched) or may contain an alicyclic ring.

[0178] The number of carbon atoms in the alkyl group which may have a substituent is preferably 1 or more, more preferably 3 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less. In addition, the number of carbon atoms in the aryl group which may have a substituent is preferably 5 or more, more preferably 6 or more, preferably 20 or less, more preferably 12 or less, and further preferably 8 or less.

[0179] Examples of the alicyclic ring include cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and the above rings having a hydrocarbon group. In addition, the alicyclic ring may be a polycyclic ring such as an adamantyl ring and a methyladamantyl ring.

[0180] Examples of the substituent which the alkyl group and the aryl group may have include a halogen atom, a hydrocarbon group having 1 to 8 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a carboxylate group having 1 to 8 carbon atoms, a sulfonate group having 1 to 8 carbon atoms, a carbonyl group having 1 to 8 carbon atoms, an amide group having 1 to 8 carbon atoms, an amino group having 1 to 8 carbon atoms, a thioether group having 1 to 8 carbon atoms, a phosphate group having 1 to 8 carbon atoms, an alkylsilyl group having 1 to 8 carbon atoms, and an alkoxysilyl group having 1 to 8 carbon atoms.

[0181] Among them, from the perspective of being able to easily obtain the composition of the present invention having excellent bonding strength with a layer containing at least one resin selected from fluororesins, LCP, ABS-based resins and polyketone-based resins, the above-mentioned R4 is preferably an unbranched and uncyclic alkyl group, and more preferably an unbranched and uncyclic alkyl group having 3 to 7 carbon atoms.

[0182] In addition, from the perspectives of improving the stability of the carbodiimide group in the air and during heating, improving the yield when synthesizing the modified body of the present invention, and reducing the manufacturing cost, the above-mentioned R4 is preferably a branched but ringless alkyl group, and more preferably a branched but ringless alkyl group having 3 to 7 carbon atoms.

[0183] It should be noted that when the above R4 has no ring, the steric hindrance caused by the ring structure can be suppressed, thereby improving the reactivity of the carbodiimide group.

[0184] Preferred examples of the unbranched and ring-free alkyl group include n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl and n-nonyl.

[0185] Examples of the branched but ringless alkyl group include isopropyl, sec-butyl, isobutyl, tert-butyl, 1-methylbutyl, 1,2-dimethylpropyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 2,2-dimethylpropyl, 1-methylpentyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 1,2,2-trimethylpropyl, 2-methylpentyl, 2,2-dimethylbutyl, butyl, 2,3-dimethylbutyl, 2-ethylbutyl, 3-methylpentyl, 3,3-dimethylbutyl, 4-methylpentyl, 1-ethyl-2-methylpropyl, 1-ethylbutyl, 1,1-dimethylbutyl, 1,1,2-trimethylpropyl, 1-ethyl-1-methylpropyl, 1-methylhexyl, 1,2-dimethylpentyl, 1,3-dimethylpentyl, 1,4-dimethylpentyl, 1,2,3-trimethylbutyl, 1, 2,2-trimethylbutyl, 1,3,3-trimethylbutyl, 2-methylhexyl, 2,3-dimethylpentyl, 2,4-dimethylpentyl, 2,3,3-trimethylbutyl, 1,1-dimethylpentyl, 1,1,2-trimethylbutyl, 1,1,3-trimethylbutyl, 1,1,2,2-tetramethylpropyl, 2,2-dimethylpentyl, 2,2,3-trimethylbutyl, 3-methylhexyl, 3,4-dimethylpentyl, 3 ,3-dimethylpentyl, 1-ethylpentyl, 1-ethyl-2-methylbutyl, 1-ethyl-3-methylbutyl, 1-ethyl-2,2-dimethylpropyl, 2-ethylpentyl, 2-ethyl-3-methylbutyl, 1-ethyl-1-methylbutyl, 1-ethyl-1,2-dimethylpropyl, 3-ethylpentyl, 1,1-diethylpropyl, 2,2-diethylpropyl, 1-propylbutyl, diisopropylmethyl, 1-isopropylbutyl.

[0186] In formula (2), m is an integer of 2 or more, and is preferably an integer of 2 to 6, more preferably an integer of 2 to 4, and particularly preferably 2, from the viewpoints of solubility and availability of the carbodiimide monomer, and ease of purification of the obtained graft modified product.

[0187] [Base polymer]

[0188] The base polymer before graft modification with the carbodiimide monomer is at least one polymer selected from polyolefins. Specific examples of the olefins include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene and 4-methyl-1-pentene.

[0189] The polyolefin may be a homopolymer of these olefins, a copolymer of two or more of these olefins, or a copolymer of one or more of these olefins and one or more of the following comonomers. The polyolefin is preferably at least one polymer selected from ethylene polymers, propylene polymers and butene polymers. When a solvent is used in the grafting reaction, it is more preferably at least one polymer selected from ethylene polymers and propylene polymers from the perspectives of excellent solubility in the solvent and excellent separation from impurities after the grafting reaction.

[0190] The base polymer of the modified product of the present invention may be two or more types, but is usually one type.

[0191] From the viewpoint of better exerting the effects of the present invention, the base polymer is preferably a polymer that does not contain at least one group containing activated hydrogen selected from the group consisting of a carboxyl group, an acid anhydride group, an amino group, a hydroxyl group, and a thiol group.

[0192] In addition, from the perspective of better exerting the effects of the present invention, the above-mentioned base polymer is also preferably a polymer that does not contain carboxylic acid derivative groups such as acyl halides, amides, imides, esters, and groups such as epoxy groups that are easily converted into groups with activated hydrogen by water, etc.

[0193] From the viewpoint of easy synthesis of the modified product of the present invention, the weight average molecular weight (Mw) of the base polymer is not limited but is preferably 100,000 or more, more preferably 150,000 or more, and preferably 1,000,000 or less, more preferably 700,000 or less.

[0194] For the same reason, the number average molecular weight (Mn) of the base polymer is also not limited but is preferably 10,000 or more, more preferably 20,000 or more, and is preferably 500,000 or less, more preferably 300,000 or less.

[0195] The molecular weight distribution (Mw / Mn) of the base polymer is not limited but is preferably 1.5 or more, more preferably 2.0 or more, and is preferably 7.0 or less, more preferably 6.0 or less.

[0196] The above-mentioned Mw and Mn are values ​​measured using HLC-8321GPC / HT gel permeation chromatograph (GPC) manufactured by Tosoh Corporation under the following conditions.

[0197] Separation columns: TSKgel GMH6-HT (2 columns) and TSKgel GMH6-HTL (2 columns) (both 7.5 mm I.D. × 30 cm, manufactured by Tosoh Corporation, Japan)

[0198] Column temperature: 140°C

[0199] Mobile phase: o-dichlorobenzene (containing 0.025% butylated hydroxytoluene (BHT))

[0200] Development rate: 1.0mL / min

[0201] Sample concentration: 0.1% (w / v)

[0202] Sample injection volume: 0.4mL

[0203] Detector: Differential refractometer

[0204] Equipment calibration: The instrument was calibrated using monodisperse polystyrene (#3std set manufactured by Tosoh Corporation, Japan).

[0205] The base polymer can be synthesized by a conventionally known method, or a commercially available product can be used.

[0206] As the above-mentioned conventional known methods, there are no restrictions, but for example, methods using a coordination polymerization catalyst system containing a transition metal can be cited. Specifically, a method of synthesizing by polymerizing or copolymerizing olefins such as ethylene and propylene with the following comonomers as required in the presence of a catalyst such as a magnesium chloride-supported titanium catalyst, a vanadium-based catalyst containing a soluble vanadium compound and an alkylaluminum halide, or a metallocene catalyst containing a metallocene compound and an organic aluminum oxide compound can be cited.

[0207] The raw materials of the base polymer (for example, olefins and monomers such as the comonomer described below) may be only biomass-derived raw materials, only fossil fuel-derived raw materials, or both biomass-derived raw materials and fossil fuel-derived raw materials.

[0208] From the viewpoint of reducing environmental load (mainly reducing greenhouse gases), the base polymer is preferably a polymer made from a biomass-derived raw material.

[0209] [Ethylene polymers]

[0210] Above-mentioned ethylene-based polymer is not particularly limited, as long as the structural unit content in ethylene source in this polymkeric substance is the polymkeric substance more than 50 mass %, can be ethylene homopolymer, also can be the multipolymer of ethylene and comonomer.In the situation of multipolymer, its structure is not particularly limited.

[0211] Examples of the comonomer include at least one monomer selected from propylene, α-olefins having 4 to 20 carbon atoms, and conjugated polyenes. Among them, propylene and α-olefins having 4 to 20 carbon atoms are preferred.

[0212] The α-olefins having 4 to 20 carbon atoms may be linear or branched, and examples thereof include 1-butene, 2-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0213] From the perspectives such as pellets, powders, etc., which are not easy to agglomerate, easy to handle, the content of the structural unit in the above-mentioned comonomer source in the above-mentioned ethylene polymer is preferably below 50 mass %, more preferably below 30 mass %, particularly preferably below 20 mass %. It should be noted that the content of the structural unit in propylene source and butene source, etc. is 50 mass % ethylene polymer, which is also referred to as ethylene polymer in this manual.

[0214] [Propylene polymer]

[0215] The propylene polymer is not particularly limited as long as the content of the structural unit derived from propylene in the polymer is more than 50% by mass, and can be a propylene homopolymer or a copolymer of propylene and a comonomer. The structure of these (co)polymers is not particularly limited.

[0216] Examples of the comonomer include at least one monomer selected from ethylene, α-olefins having 4 to 20 carbon atoms, and conjugated polyenes. Among them, ethylene and α-olefins having 4 to 20 carbon atoms are preferred.

[0217] Examples of the α-olefin having 4 to 20 carbon atoms include the same α-olefin having 4 to 20 carbon atoms as mentioned above in the section of the ethylene-based polymer.

[0218] From the perspective of pellets, powders, etc., which are not prone to agglomeration and easy handling, the content of the structural unit derived from the comonomer in the propylene polymer is preferably 50% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less. It should be noted that the propylene polymer having a content of 50% by mass of the structural unit derived from butene is also referred to as a propylene polymer in this specification.

[0219] [Butene polymer]

[0220] The butene polymer is not particularly limited, as long as the content of structural units derived from butene in the polymer is more than 50% by mass, and can be a homopolymer of butene, especially 1-butene, or a copolymer of butene (especially 1-butene) and a comonomer. The structure of these (co)polymers is not particularly limited.

[0221] Examples of the comonomer include at least one monomer selected from ethylene, propylene, α-olefins having 5 to 20 carbon atoms, and conjugated polyenes. Among them, ethylene, propylene, and α-olefins having 5 to 20 carbon atoms are preferred.

[0222] Examples of the α-olefin having 5 to 20 carbon atoms include the same α-olefin having 5 to 20 carbon atoms as mentioned above in the section of the ethylene-based polymer.

[0223] From the viewpoint of preventing pellets, powders, etc. from agglomerating and being easy to handle, the content of the structural unit derived from the comonomer in the butene-based polymer is preferably 50% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less.

[0224] <Method for synthesizing the modified product of the present invention>

[0225] There is no particular limitation on the method for synthesizing the modified product of the present invention, as long as a grafted modified product can be obtained after the base polymer is grafted and modified by the carbodiimide monomer. However, from the perspective of being able to easily synthesize the modified product of the present invention, it is preferred to add a free radical initiator and the carbodiimide monomer to a solution or dispersion obtained by dissolving or dispersing the base polymer in a solvent, and more preferably to a solution obtained by dissolving the base polymer in an organic solvent to react (grafting reaction). It should be noted that in the case of using a reaction device with a stirring capability that allows the base polymer to flow evenly, a solvent may not be used.

[0226] By initiating graft polymerization through the above method, a graft-modified product can be obtained.

[0227] From the perspectives of being able to easily obtain the modified product of the present invention having a grafting rate within the above-mentioned range and being able to suppress the formation of the polymer of the carbodiimide monomer itself (hereinafter also referred to as "non-grafted polymer"), the amount of the carbodiimide monomer used in the above-mentioned grafting reaction is preferably 10 to 1000 mol, more preferably 10 to 800 mol relative to 1 mol of the base polymer.

[0228] Examples of the free radical initiator include organic peroxides and azo compounds, and specific examples include benzoyl peroxide, dichlorobenzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)-3-hexyne, 1,4-di(tert-butylperoxide isopropyl)benzene, lauroyl peroxide, tert-butyl peracetate, 2,5-dimethyl-2,5-di(tert-butylperoxide)- Organic peroxides such as 3-hexyne, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexane, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl perisobutyrate, tert-butyl persecanoate, tert-butyl peroxypivalate, isopropyl peroxypivalate, tert-butyl peroxydiethylacetate, tert-butyl peroxyisopropyl monocarbonate (tert-butyl peroxyisopropyl monocarbonate); azo compounds such as azobisisobutyronitrile and dimethyl azoisobutyrate. Among them, organic peroxides such as diisopropyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxide)-3-hexyne, 2,5-dimethyl-2,5-di(tert-butyl peroxide)hexane, 1,4-di(tert-butyl peroxideisopropyl)benzene, and tert-butyl peroxyisopropyl monocarbonate are preferred.

[0229] The above-mentioned radical initiators may be used alone or in combination of two or more.

[0230] From the perspective of being able to efficiently initiate the grafting reaction and easily obtain the modified product of the present invention with a grafting rate within the above-mentioned range, the amount of the free radical initiator used in the above-mentioned grafting reaction is preferably 0.01 mol or more, more preferably 0.05 mol or more, and preferably 0.7 mol or less, more preferably 0.5 mol or less relative to 1 mol of the carbodiimide monomer.

[0231] As the above-mentioned organic solvent, it is preferred that the organic solvent does not significantly hinder the grafting reaction of the above-mentioned carbodiimide monomer and has affinity with the base polymer in the temperature range where the grafting reaction is carried out. Specific examples of such organic solvents include aromatic hydrocarbon solvents such as benzene, toluene, and xylene; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, octane, nonane, and decane; alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and decalin; chlorinated hydrocarbon solvents such as chlorobenzene, dichlorobenzene, trichlorobenzene, dichloromethane, chloroform, carbon tetrachloride, and tetrachloroethylene; alcohol solvents such as methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and tert-butanol; ketone solvents such as acetone, butanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and dimethyl phthalate; and ether solvents such as dimethyl ether, diethyl ether, di-n-pentyl ether, tetrahydrofuran, and dihydroxyanisole. In addition, water can also be used as a solvent for suspension polymerization or emulsion polymerization. These solvents may be used alone or in combination of two or more. It is preferred that the reaction liquid be homogeneous by using these solvents, but a plurality of heterogeneous phases may be formed.

[0232] In order to carry out the graft reaction in a region where the liquid containing the base polymer can be uniformly stirred, the concentration of the base polymer in the liquid is usually set to 50 to 500 g / L, and preferably to 200 to 500 g / L to achieve a high grafting rate.

[0233] Although the radical initiator and the carbodiimide monomer may be added all at once to the liquid containing the base polymer (or the base polymer itself) to initiate the grafting reaction, in order to achieve a high grafting rate, it is preferred to add them successively over a period of about 0.1 to 5 hours to carry out the grafting reaction.

[0234] It should be noted that, when the free radical initiator and the carbodiimide monomer are added to the base polymer or to the liquid obtained by dissolving or dispersing the base polymer in the solvent, there is no particular restriction on the order of adding these additives. For example, when adding them one by one as described above, the free radical initiator and the carbodiimide monomer can be added one by one, or the free radical initiator can be added one by one after adding the carbodiimide monomer first.

[0235] The grafting reaction is usually carried out at a temperature of 60°C or higher, preferably 100°C or higher, usually 200°C or lower, preferably 160°C or lower, for usually 2 hours or more, preferably 3 hours or more, usually 10 hours or less, preferably 8 hours or less.

[0236] The modified product of the present invention obtained by the above grafting reaction can be purified and separated by known methods such as filtration, centrifugal separation, reprecipitation and / or washing to remove the used solvent, unreacted free radical initiator and carbodiimide monomer, and by-product non-grafted polymer.

[0237] In this case, from the perspective of easily obtaining the present invention composition having the above-mentioned better bonding performance, it is necessary to purify and isolate the modified product of the present invention so that the content of the non-grafted polymer contained in the modified product is preferably 5 mass % or less, more preferably 2 mass % or less.

[0238] <Method for producing laminate of the present invention>

[0239] The method for manufacturing the above-mentioned laminate varies depending on the shape, size, required physical properties, etc. of the final product, and is therefore not particularly limited. However, from the perspective of being able to easily manufacture the laminate of the present invention having the required physical properties with excellent interlayer adhesion, it is preferably manufactured by a method comprising the steps of co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing at least one resin selected from fluororesins, LCP, ABS resins and polyketone resins with the above-mentioned composition of the present invention.

[0240] As the co-extrusion molding, lamination molding, blow molding and coinjection molding, any conventionally known method may be employed.

[0241] When a resin composition containing at least one resin selected from a fluororesin and an LCP is used, the temperature during production of the laminate is preferably 180 to 350°C, more preferably 200 to 320°C.

[0242] When a resin composition containing at least one resin selected from ABS resins and polyketone resins is used, the temperature during production of the laminate is preferably 170 to 280°C, more preferably 200 to 260°C.

[0243] Examples of the lamination molding include the following methods (1) and (2).

[0244] (1) A method of heat-sealing the preformed layers (A) and (B) at a temperature higher than the melting temperature of at least one of the preformed layers (A) and (B) using a roll forming device, a compression forming device or the like.

[0245] (2) A method of heat-fusion bonding a preformed layer (A) or layer (B) to another layer obtained by extrusion molding or calendar molding.

[0246] In the process of manufacturing a laminate by pressing (thermal bonding) the preformed layer (A) and layer (B) using the compression molding device in the above-mentioned method (1), when a modified fluororesin sheet is used as layer (A), for example, and thermal bonding is performed at a temperature of 220°C, a layer with excellent bonding strength can be formed even if the thermal bonding time is set to a short time of preferably less than 60 seconds, more preferably less than 30 seconds, and further preferably less than 15 seconds.

[0247] In addition, in the process of manufacturing a laminate by pressing (thermal bonding) the preformed layer (A) and layer (B) using the compression molding device in the above-mentioned method (1), when a polyketone sheet is used as layer (A), for example, and thermal bonding is performed at a temperature of 260°C, a layer with excellent bonding strength can be formed even when the thermal bonding time is set to a short time of preferably less than 30 seconds, more preferably less than 15 seconds.

[0248] As the above-mentioned co-extrusion molding, for example, a method in which a resin composition containing at least one resin selected from fluororesin, LCP, ABS resin and polyketone resin is simultaneously extruded and molded with the composition of the present invention using a multilayer extrusion molding device to form heat-fused layers (A) and (B).

[0249] As the above-mentioned co-injection molding, for example, there can be mentioned a method in which a resin composition containing at least one resin selected from fluororesins, LCP, ABS resins and polyketone resins that has been melted is injected into a mold at the same time or with staggered injection timing (for example, double-layer injection molding, sandwich injection molding).

[0250] Example

[0251] Hereinafter, an embodiment of the present invention will be described based on examples, but the present invention is not limited to these examples.

[0252] <Method for measuring grafting rate>

[0253] Using an AVANCE IIIcryo-500 nuclear magnetic resonance apparatus (500 MHz) manufactured by Bruker Biospin Co., Ltd., under the measurement conditions of 1,1,2,2-tetrachloroethane-d2 as the measurement solvent, 120°C as the measurement temperature, 20 ppm as the spectrum width, 7.0 seconds as the pulse period, and 5.00 μsec as the pulse width (45° pulse), the following graft polymers obtained in the synthesis example were obtained: 1 H-NMR spectrum. In the obtained spectrum, the grafting rate of the grafted polymer obtained in the following synthesis example was calculated based on the peak intensity ratio of the protons from the hydrocarbon groups bonded to the carbodiimide groups present at 3.0 ppm to 4.0 ppm and the protons from all hydrocarbon groups bonded to the base polymer present at 0.3 ppm to 2.5 ppm.

[0254] [Synthesis example 1]

[0255] 25.0 g of polypropylene (base polymer, propylene homopolymer, Mw: 313,000, Mn: 70,800, Mw / Mn: 4.42) and 110 mL of xylene were added to a 500 mL glass container, and the inside of the container was replaced with nitrogen. Then, the internal temperature of the container was raised to 120°C, and while maintaining this temperature, the mixture was stirred at a stirring speed of 400 rpm using a double anchor stirring blade, and 28.1 mmol of vinylphenylcyclohexylcarbodiimide and 2.2 mmol of tert-butylperoxyisopropylmonocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene were added over 10 minutes. Then, after stirring for another 3 hours, 200 mL of toluene was added to dilute the reaction solution.

[0256] The internal temperature of the container was then cooled to 50°C, and after the pressure was removed, the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated 3 times for the obtained solid component.

[0257] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.13 g of a graft polymer (P-1). The graft ratio was 1.5% by mass.

[0258] [Synthesis example 2]

[0259] 15.0 g of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) and 62 mL of xylene were added to a 500 mL glass container, and the inside of the container was replaced with nitrogen. Then, the internal temperature of the container was raised to 120° C., and while maintaining this temperature, 22.1 mmol of ethyl methacrylate tert-butylcarbodiimide was added, and then stirred at a stirring speed of 400 rpm using a double anchor stirring blade, while 9.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, after stirring for another 3 hours, 150 mL of xylene was added to dilute the reaction solution.

[0260] Then, the internal temperature of the container was cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated 3 times for the obtained solid component.

[0261] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 15.37 g of a graft polymer (P-2). The graft ratio was 1.3% by mass.

[0262] [Synthesis example 3]

[0263] 25.0 g of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) and 120 mL of xylene were added to a 500 mL glass container, and the inside of the container was replaced with nitrogen. Then, the internal temperature of the container was raised to 120° C., and while maintaining this temperature, 33.4 mmol of glycidyl methacrylate was added, and then, while stirring at a stirring speed of 400 rpm using a double anchor stirring blade, 11 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added dropwise over 10 minutes. Then, stirring was continued for another 3 hours.

[0264] Next, 200 mL of xylene was added, and the internal temperature of the container was slowly cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and stirred for 10 minutes. The reaction liquid was then filtered to separate into a solid component and a filtrate. The obtained solid component was washed three times with 400 mL of acetone to remove unreacted glycidyl methacrylate and homopolymer of glycidyl methacrylate.

[0265] The obtained solid component was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.26 g of a graft polymer (CP-1). The graft ratio was 1.0% by mass.

[0266] [Synthesis Example 4]

[0267] 25.0 g of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) and 110 mL of xylene were added to a 500 mL glass container, and the inside of the container was replaced with nitrogen. Then, the internal temperature of the container was raised to 120° C., and while maintaining this temperature, 33.4 mmol of maleic anhydride was added, and then, while stirring at a stirring speed of 400 rpm using a double anchor stirring blade, 2.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added dropwise over 10 minutes. Then, stirring was continued for another 3 hours.

[0268] Next, 200 mL of xylene was added, and the internal temperature of the container was slowly cooled to 50°C, and the slurry reaction solution was taken out. 400 mL of acetone was added to the obtained reaction solution, and stirred for 10 minutes. The reaction solution was then filtered to separate into a solid component and a filtrate. The obtained solid component was washed three times with 400 mL of acetone to remove unreacted maleic anhydride.

[0269] The obtained solid component was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.01 g of a graft polymer (CP-2). The graft ratio was 0.62% by mass.

[0270] [Synthesis example 5]

[0271] 22.5 g of polypropylene (base polymer, Mw: 157,000, Mn: 31,000, Mw / Mn: 5.06) and 62 mL of xylene were added to a 500 mL separatory bottle, and the separatory bottle was replaced with nitrogen. Then, the internal temperature was raised to 120°C. While maintaining this temperature, 44.2 mmol of ethyl methacrylate tert-butylcarbodiimide was added, and then stirred at a stirring speed of 400 rpm using a double anchor stirring blade, and 18.4 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added for 10 minutes. Then, after stirring for another 3 hours, 100 mL of xylene was added to dilute the reaction solution.

[0272] Then, the internal temperature of the separatory bottle was cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated 3 times for the obtained solid component. Through these four filtrations, unreacted ethyl methacrylate tert-butylcarbodiimide and homopolymers of ethyl methacrylate tert-butylcarbodiimide were removed.

[0273] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 23.18 g of a graft polymer (P-3). The graft rate was 4.0% by mass.

[0274] [Synthesis example 6]

[0275] 25.0 g of LLDPE (base polymer, copolymer species: 1-hexene, copolymer amount: 1.6% by mass, Mw: 164,000, Mn: 63,000, Mw / Mn: 2.60) and 110 mL of xylene were added to a 500 mL glass container, and the inside of the container was replaced with nitrogen. Then, the internal temperature of the container was raised to 120°C, and 35.0 mmol of ethyl methacrylate tert-butylcarbodiimide was added while maintaining the temperature. Then, while stirring at a stirring speed of 400 rpm using a double anchor stirring blade, 2.2 mmol of tert-butyl peroxyisopropyl monocarbonate (PERBUTYL I, manufactured by NOF Corporation) dissolved in 10 mL of xylene was added over 10 minutes. Then, after stirring for another 3 hours, 200 mL of xylene was added to dilute the reaction solution.

[0276] Then, the internal temperature of the container was cooled to 50°C, and the slurry-like reaction liquid was taken out. 400 mL of acetone was added to the obtained reaction liquid, and after stirring for 10 minutes, the stirred liquid was filtered to separate into a solid component and a filtrate. The steps from adding acetone to filtering were repeated 3 times for the obtained solid component.

[0277] The solid component after the fourth filtration was dried in a vacuum dryer at 90° C. for 10 hours to obtain 25.49 g of a graft polymer (P-4). The graft ratio was 1.7% by mass.

[0278] <mfr>

[0279] The MFR (g / 10 min) of the bonding compositions obtained in the following Examples and Comparative Examples was measured in accordance with JIS K 7210 under the conditions of 190° C. and a load of 2.16 kg.

[0280] <Carbodiimide Group Content>

[0281] The carbodiimide group content (mmol) per 100 g of the bonding compositions obtained in the following Examples and Comparative Examples was calculated by the following formula (I). The results are shown in Tables 1 to 5 as carbodiimide group content (mmol / 100 g).

[0282] (Grafting ratio of grafted modified body used in the bonding composition [mass %] / molecular weight of carbodiimide monomer used in the synthesis of the grafted modified body) × 100 × amount of grafted modified body used in the bonding composition [mass %] / 10 (I)

[0283] <density>

[0284] The density (g / cm 3 ) was measured in accordance with JIS K7210. The results are shown in Tables 1 to 5.

[0285] [Example 1]

[0286] 12 parts by mass of the graft polymer (P-1) prepared in Synthesis Example 1 and 88 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) were kneaded using a grinder (LABO PLASTOMILL) at a temperature of 190° C., a screw speed of 60 rpm, and a kneading time of 10 minutes to obtain a bonding composition C-1.

[0287] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-1 was 0.6 g / 10 min, and the density was 0.893 g / cm 3 The carbodiimide content in each 100 g of the composition is 0.8 mmol.

[0288] [Example 2]

[0289] A bonding composition C-2 was obtained in the same manner as in Example 1 except that 13 parts by mass of the graft polymer (P-2) prepared in Synthesis Example 2 and 87 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0290] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-2 was 2.0 g / 10 min, and the density was 0.892 g / cm 3 The carbodiimide content in each 100 g of the composition is 0.8 mmol.

[0291] [Example 3]

[0292] A bonding composition C-3 was obtained in the same manner as in Example 1 except that 16 parts by mass of the graft polymer (P-3) prepared in Synthesis Example 5 and 84 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 5) were used.

[0293] The MFR (190°C, 2.16 kg load) of the obtained bonding composition C-3 was 3.5 g / 10 min, and the density was 0.902 g / cm 3 The carbodiimide content in each 100 g of the composition is 3.1 mmol.

[0294] [Example 4]

[0295] A bonding composition C-4 was obtained in the same manner as in Example 1 except that 16 parts by mass of the graft polymer (P-4) prepared in Synthesis Example 6 and 84 parts by mass of LLDPE (the same polymer as the base polymer used in Synthesis Example 6) were used.

[0296] The density of the obtained bonding composition C-4 was 0.902 g / cm 3 The carbodiimide content in each 100 g of the composition is 1.3 mmol.

[0297] [Comparative Example 1]

[0298] A bonding composition CC-1 was obtained in the same manner as in Example 1 except that 12 parts by mass of the graft polymer (CP-1) prepared in Synthesis Example 3 and 88 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0299] The MFR (190°C, 2.16 kg load) of the obtained bonding composition CC-1 was 1.9 g / 10 min, and the density was 0.892 g / cm 3 The epoxy group content in each 100 g of the composition is 0.8 mmol, and the composition does not contain a graft modified body modified by a carbodiimide monomer.

[0300] [Comparative Example 2]

[0301] A bonding composition CC-2 was obtained in the same manner as in Example 1 except that 13 parts by mass of the graft polymer (CP-2) prepared in Synthesis Example 4 and 87 parts by mass of polypropylene (the same polymer as the base polymer used in Synthesis Example 1) were used.

[0302] The MFR (190°C, 2.16 kg load) of the obtained bonding composition CC-2 was 2.1 g / 10 min, and the density was 0.892 g / cm 3 The acid anhydride group content in each 100 g of the composition is 0.8 mmol, and the composition does not contain a graft modified body modified by a carbodiimide monomer.

[0303] [Comparative Example 3]

[0304] Lotader (manufactured by Arkema, density 0.940 g / cm 3 , the epoxy group content per 100 g of the composition was 56 mmol, and there was no graft modified product modified with a carbodiimide monomer) as a bonding composition CC-3.

[0305] <Joint Evaluation>

[0306] Preparation of pressed sheets

[0307] Each bonding composition obtained in Examples 1 to 2 and Comparative Example 2 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 80 mm.

[0308] Preparation of fluororesin laminate 1

[0309] An acid-modified fluororesin sheet (product name: Fluon LH-8000, manufactured by AGC Corporation) having a thickness of 500 μm, a length of 80 mm, and a width of 80 mm was used.

[0310] The modified fluororesin sheet and the pressed sheet are stacked, and the stacked laminate is The sheets were sandwiched and heat-bonded for 15 seconds, 30 seconds, and 60 seconds using a heat-bonding machine with the upper and lower platens set at 220°C, thereby producing a fluororesin laminate 1 consisting of two layers.

[0311] Peel test

[0312] The peel strength between the modified fluororesin sheet and the pressed sheet of the prepared fluororesin laminate 1 was measured by T-peeling at a peeling ambient temperature of 23°C, a peeling speed of 300 mm / min, and a peeling width of 15 mm. The results are shown in Table 1. It should be noted that the situation where the modified fluororesin sheet breaks not at the interface between the modified fluororesin sheet and the pressed sheet but at the modified fluororesin itself due to the strong bonding force is indicated as "fluororesin breakage".

[0313] [Table 1]

[0314]

[0315] Preparation of pressed sheets

[0316] Each bonding composition obtained in Examples 2 to 3 and Comparative Examples 1 to 2 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 20 mm.

[0317] Preparation of fluororesin laminate 2

[0318] An acid-modified fluororesin sheet (product name: Fluon LH-8000, manufactured by AGC Corporation) having a thickness of 500 μm, a length of 80 mm, and a width of 20 mm was used.

[0319] The modified fluororesin sheet, the pressed sheet and the modified fluororesin sheet are stacked in this order, and the stacked laminate is The sheets were sandwiched and heat-bonded for 2 seconds, 3 seconds, and 5 seconds using a heat-bonding machine with the upper and lower platens set to 220° C., thereby producing a fluororesin laminate 2 consisting of three layers.

[0320] Peel test

[0321] The peel strength between the modified fluororesin sheet and the pressed sheet was measured by performing T-type peeling on the modified fluororesin sheet on the upper side of the prepared fluororesin laminate 2 (modified fluororesin sheet on the press plate (upper) side) and the pressed sheet under the conditions of a peeling environment temperature of 23°C, a peeling speed of 300mm / min, and a peeling width of 15mm. The results are shown in Table 2. It should be noted that the situation where the modified fluororesin sheet breaks not at the interface between the modified fluororesin sheet and the pressed sheet but at the modified fluororesin itself due to the strong bonding force is represented as "fluororesin breakage".

[0322] [Table 2]

[0323]

[0324] Preparation of pressed sheets

[0325] Each bonding composition obtained in Examples 1 to 2 and Comparative Examples 1 to 2 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 80 mm.

[0326] Preparation of LCP laminates

[0327] An LCP sheet (product name: SUMIKA SUPER LCP: S6000, manufactured by Sumitomo Chemical Co., Ltd.) having a thickness of 500 μm, a length of 80 mm, and a width of 80 mm was used.

[0328] The LCP sheet and the pressed sheet are stacked, and the laminated body formed by stacking these sheets is used The sheets were clamped and heat-bonded for 15 seconds or 30 seconds using a heat bonding machine with the upper and lower platens set to 300°C to produce an LCP laminate consisting of two layers.

[0329] Peel test

[0330] The peel strength between the LCP sheet and the pressed sheet of the prepared LCP laminate was measured by T-peeling at a peeling ambient temperature of 23°C, a peeling speed of 300 mm / min, and a peeling width of 15 mm. The results are shown in Table 3.

[0331] [Table 3]

[0332]

[0333] Preparation of pressed sheets

[0334] Each bonding composition obtained in Examples 1, 2, 4 and Comparative Examples 1 to 3 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 80 mm.

[0335] Preparation of ABS resin laminate

[0336] An ABS resin sheet (product name: UMG ABS: EX18A, manufactured by Techno UMG Co., Ltd.) having a thickness of 500 μm, a length of 80 mm, and a width of 80 mm was used.

[0337] The ABS resin sheet and the pressed sheet are stacked, and the laminated body formed by stacking these sheets is used The sheets were sandwiched and heat-bonded for 30 seconds or 60 seconds using a heat bonding machine with the upper and lower platens set at 230° C. to produce an ABS resin laminate consisting of two layers.

[0338] Peel test

[0339] The peel strength between the ABS resin sheet and the pressed sheet of the prepared ABS resin laminate was measured by T-peeling at a peeling ambient temperature of 23° C., a peeling speed of 300 mm / min, and a peeling width of 15 mm. The results are shown in Table 4.

[0340] [Table 4]

[0341]

[0342] Preparation of pressed sheets

[0343] Each bonding composition obtained in Examples 1 to 2 and Comparative Examples 1 to 2 was press-molded under the conditions of a temperature of 180°C, a pressure of 4 MPa, a preheating time of 5 minutes, and a pressing time of 3 minutes, and then quenched in a press-molding machine set at 20°C to produce a pressed sheet with a thickness of 500 μm, a length of 80 mm, and a width of 80 mm.

[0344] Preparation of polyketone laminates

[0345] A polyketone sheet (product name: AKROTEK: PK-HM, manufactured by AKRO-PLASTIC Co., Ltd.) having a thickness of 500 μm, a length of 80 mm, and a width of 80 mm was used.

[0346] The polyketone sheet and the pressed sheet are stacked, and the laminated body formed by stacking these sheets is used The sheets were clamped and heat-bonded for 15 seconds or 30 seconds using a heat-bonding machine with the upper and lower platens set to 230°C or 260°C to produce a polyketone laminate consisting of two layers.

[0347] Peel test

[0348] The polyketone sheet and the pressed sheet of the prepared polyketone laminate were subjected to T-type peeling at a peeling ambient temperature of 23°C, a peeling speed of 300 mm / min, and a peeling width of 15 mm to measure the peeling strength between the polyketone sheet and the pressed sheet. The results are shown in Table 5. It should be noted that the situation in which the polyketone sheet itself is broken rather than at the interface between the polyketone sheet and the pressed sheet due to the strong bonding force is expressed as "polyketone resin fracture".

[0349] [Table 5]

[0350] < / mfr>

Claims

1. A laminate, wherein: The invention comprises: a layer (A) containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins, and a bonding layer (B) containing a bonding composition, At least a portion of the bonding layer (B) is in contact with the layer (A), The bonding composition satisfies the following requirements (i) to (iii): (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond; (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition; (iii) Density: 0.870 to 0.940 g / cm 3 .

2. The laminate according to claim 1, wherein The carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2). In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

3. The laminate according to claim 1 or 2, wherein: The layer (A) is made of fluororesin.

4. The laminate according to claim 3, wherein: The fluororesin is an acid-modified modified fluororesin.

5. The laminate according to claim 1 or 2, wherein: The layer (A) is made of a liquid crystal polymer.

6. The laminate according to claim 1 or 2, wherein: The layer (A) is made of acrylonitrile-butadiene-styrene copolymer resin.

7. The laminate according to claim 1 or 2, wherein: The layer (A) is made of a polyketone resin.

8. The laminate according to claim 1 or 2, wherein: The laminate is obtained by co-extrusion molding, lamination molding, blow molding or co-injection molding.

9. A method for producing a laminate, wherein: The laminate comprises: a layer (A) containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins; and a bonding layer (B) containing a bonding composition. At least a portion of the bonding layer (B) is in contact with the layer (A), The manufacturing method comprises the steps of: co-extrusion molding, lamination molding, blow molding or co-injection molding of a resin composition containing at least one resin selected from fluororesins, liquid crystal polymers, acrylonitrile-butadiene-styrene copolymer resins and polyketone resins with the bonding composition; The bonding composition satisfies the following requirements (i) to (iii): (i) comprising a graft modified body formed by modifying at least one base polymer selected from polyolefins with a carbodiimide monomer having a carbodiimide group and a polymerizable double bond; (ii) containing 0.1 to 50 mmol of carbodiimide groups per 100 g of the bonding composition; (iii) Density: 0.870 to 0.940 g / cm 3 .

10. The method for producing a laminate according to claim 9, wherein: The carbodiimide monomer is at least one monomer selected from the group consisting of a compound represented by the following formula (1) and a compound represented by the following formula (2). In formula (1), R1 is a hydrogen atom or a methyl group, R2 is an alkyl group or an aryl group which may have a substituent, and in formula (2), R3 is a hydrogen atom or a methyl group, R4 is an alkyl group or an aryl group which may have a substituent, and m is an integer greater than 2.

11. The method for producing a laminate according to claim 9 or 10, wherein: The layer (A) is made of fluororesin.

12. The method for producing a laminate according to claim 11, wherein: The fluororesin is an acid-modified modified fluororesin.

13. The method for producing a laminate according to claim 9 or 10, wherein: The layer (A) is made of a liquid crystal polymer.

14. The method for producing a laminate according to claim 9 or 10, wherein: The layer (A) is made of acrylonitrile-butadiene-styrene copolymer resin.

15. The method for producing a laminate according to claim 9 or 10, wherein: The layer (A) is made of a polyketone resin.

Citation Information

Patent Citations

  • Laminate and method of manufacturing the same

    JP2013184466A

  • Adhesive resin and adhesive resin composition for liquid crystalline polymer

    WO2003078488A1

  • Multilayer laminate

    WO2005068191A1

  • Laminate, manufacturing method therefor, and adhesive composition

    CN108290392A

  • Carbodiimide compound and polymer thereof, gelatinous composition, ionic conductive composition, electrochemical element, and surface-modified substrate

    JP2005048127A